If `x gt= 0` , then `sqrt(x* sqrt(x* sqrt(x)))`  equals:

a. `root(8)((x^7))`

b. `xroot(4)(x)`

c. `x sqrt(x)`

d. `sqrt(x^3)`







Expert Answers

An illustration of the letter 'A' in a speech bubbles

`sqrt(x*sqrt(x*sqrtx))`

To simplify, express the radicals as exponents.

`=sqrt(x*sqrt(x*x^(1/2)))`

`=sqrt(x*(x*x^(1/2))^(1/2))`

`=(x*(x*x^(1/2))^(1/2))^(1/2)`

Since the resulting expression is nested parenthesis, start to simplify the innermost expression.

To multiply x*x^1/2, apply the properties of exponent which is a^m*a^n=a^(m+n).

`=(x*(x^(1+1/2))^(1/2))^(1/2)`

`=(x(x^(3/2))^(1/2))^(1/2)`

Then, simplify `(x^(3/2))^(1/2)` . To do so, apply  `(a^m)^n=a^(m*n)` .

`=(x*x^(3/2*1/2))^(1/2)`

`=(x*x^(3/4))^(1/2)`

Next simplify x*x^(3/4). Again, apply the rule of multiplying same base.

`=(x^(1+3/4))^(1/2)`

`=(x^(7/4))^(1/2)`

And, apply `(a^m)^n = a^(m*n)` , too.

`=x^(7/4*1/2)`

`=x^(7/8)`

Since the exponent is a fraction, express it as a radical. Note that `a^(m/n)= root(n)(a^m)` .

`=root(8)((x^7))` 

Hence,  `sqrt(x*sqrt(x*sqrtx))=root(8)((x^7))` .

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial